Determining Factors of Institutional Management of Downstream Agribusiness Subsystem in Sustainable Rice Food Business Development - Sri Indaryati; Sriati; Dessy Adriani; Riswani (Migration Letters, 2023)
One of the essential aspects of improving sustainable rice food business development is management in downstream agribusiness institutions. Previous research has shown that there is still a lack of management and institutional development of sustainable downstream agribusiness subsystems. This research aims to examine the determining factors that affect the performance of the Community Food Business Institute (LUPM) and the Sustainability of the Indonesian Community Food Business Development program (PUPM-TTI). Research location in The Metro City of Lampung Province, Indonesia. This research uses a quantitative approach. The sample number of 292 was taken from 1291 populations based on Krejcie and Morgan table guidelines. Data analysis using K-Means Cluster with SPSS 21 Program and Structure Equation Modeling (SEM) with Smart pls 3.2 Program. Data collection uses in-depth observation and interview methods. The results showed that the variables that most affect the performance of LUPM are social capital and the following sequential participation variables, transaction costs, institutional elements, and human capital. The factors that most affect the Sustainability of the PUMP-TTI program are the following participation variables order of social capital variables, human capital, transaction costs, and institutional elements. All variables have an indirect influence on PUPM-TTI sustainability through LUPM performance.